Greening ports and maritime logistics: A review. (October 2016) - Davarzani, Hoda; Fahimnia, Behnam; Bell, Michael; Sarkis, Joseph
Highlights: A systematic review of the literature of green ports and maritime logistics. Using bibliometric and network analysis tools for systemic literature mapping. We identify seminal research areas that form the foundation of the field. We find that the field is rapidly growing in a number of directions. We identify a gap between naval architects and researchers from other clusters. Abstract: This paper aims to examine the past and present research on 'green ports and maritime logistics' in order to identify established research streams and fertile research areas with potential for future investigations. Using rigorous bibliometric and network analysis tools, the paper completes a systemic mapping of the existing literature and identifies the key investigators, collaboration patterns, research clusters and interrelationships, and the "seminal research areas" that have provided the field with the foundational knowledge, concepts, theories, tools, and techniques. Major articles within each seminal research area are also identified. This will allow new researchers to quickly build understanding in a particular sub-field by reading these major articles. The findings obtained from the evolution of seminal research areas over time are important from both research and practice perspectives and can help the field grow in many dimensions.